2022
DOI: 10.1177/00332941221089282
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Mindfulness Induction as a Buffer Against Stress Among University Students With and Without a History of Self-Injury

Abstract: Stressful experiences are abundant in university and students with a history of nonsuicidal self-injury (NSSI) may be hyper-reactive to stress. While brief mindfulness inductions have been proposed as a buffer against acute stress, whether they function differently in students with a history of NSSI remains in question. This study sought to explore the impact of an online mindfulness induction on (a) two facets of state mindfulness (i.e., mind and body) and (b) state stress, following a stress induction task, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…For instance, these students may find formal mindfulness practices that are body-focused (e.g., the body scan, a common formal mindfulness practice) to be more challenging than students without a history of NSSI. To illustrate, a recent experimental study found that university students with lived experience of NSSI responded differently to a formal body scan practice relative to students without such a history (Petrovic et al, 2023). Specifically, students with a history of NSSI experienced a more pronounced increase in their awareness of their body following the body scan, relative to students without such a history.…”
Section: The Present Studymentioning
confidence: 99%
“…For instance, these students may find formal mindfulness practices that are body-focused (e.g., the body scan, a common formal mindfulness practice) to be more challenging than students without a history of NSSI. To illustrate, a recent experimental study found that university students with lived experience of NSSI responded differently to a formal body scan practice relative to students without such a history (Petrovic et al, 2023). Specifically, students with a history of NSSI experienced a more pronounced increase in their awareness of their body following the body scan, relative to students without such a history.…”
Section: The Present Studymentioning
confidence: 99%